Readmission of older patients after hospital discharge for hip fracture: a multilevel approach - Fátima de Lima Paula; Geraldo Marcelo da Cunha; Iúri da Costa Leite; Rejane Sobrino Pinheiro; Joaquim Gonçalves Valente (Universidade de São Paulo, 2016)
ABSTRACT OBJECTIVE To identify individual and hospital characteristics associated with the risk of readmission in older inpatients for proximal femoral fracture in the period of 90 days after discharge. METHODS Deaths and readmissions were obtained by a linkage of databases of the Hospital Information System of the Unified Health System and the System of Information on Mortality of the city of Rio de Janeiro from 2008 to 2011. The population of 3,405 individuals aged 60 or older, with non-elective hospitalization for proximal femoral fracture was followed for 90 days after discharge. Cox multilevel model was used for discharge time until readmission, and the characteristics of the patients were used on the first level and the characteristics of the hospitals on the second level. RESULTS The risk of readmission was higher for men (hazard ratio [HR] = 1.37; 95%CI 1.08-1.73), individuals more than 79 years old (HR = 1.45; 95%CI 1.06-1.98), patients who were hospitalized for more than two weeks (HR = 1.33; 95%CI 1.06-1.67), and for those who underwent arthroplasty when compared with the ones who underwent osteosynthesis (HR = 0.57; 95%CI 0.41-0.79). Besides, patients admitted to state hospitals had lower risk for readmission when compared with inpatients in municipal (HR = 1.71; 95%CI 1.09-2.68) and federal hospitals (HR = 1.81; 95%CI 1.00-3.27). The random effect of the hospitals in the adjusted model remained statistically significant (p < 0.05). CONCLUSIONS Hospitals have complex structures that reflect in the quality of care. Thus, we propose that future studies may include these complexities and the severity of the patients in the analysis of the data, also considering the correlation between readmission and mortality to reduce biases.